2018
DOI: 10.3389/fpsyt.2018.00434
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy in Microglia Alters Depressive-Like Behavior via BDNF Pathway in Postpartum Depression

Abstract: Postpartum depression (PPD) is associated with mood disorders and elevated inflammation. Studies have evidenced the activation/inhibition of autophagy and excessive activation of microglia to have a close relationship with depression. C57 and microglia-specific autophagy-deficient mice (Cx3Cr1Cre/+ATG5loxp/loxp) were employed to establish the chronic unpredicted mild stress depression mice model from embryonic day 7 (E7) to embryonic day 16 (E16). Fluoxetine was administered for 3 weeks (commencing from 1 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…Thus, we demonstrated that H 2 S‐enhanced hippocampal autophagy in STZ‐induced diabetic rats is achieved by upregulation of BDNF. It has been reported that BDNF promotes neuron survival through improving autophagy and that fluoxetine exerts its antidepressant effect through enhancing the autophagic pathway by upregulation of the BDNF‐TrkB pathway . Therefore, our present data indicate that the contribution of the BDNF‐TrkB pathway to the antidepressant‐like roles of H 2 S in STZ‐induced diabetic rats is achieved by promoting hippocampal autophagy (Figure ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, we demonstrated that H 2 S‐enhanced hippocampal autophagy in STZ‐induced diabetic rats is achieved by upregulation of BDNF. It has been reported that BDNF promotes neuron survival through improving autophagy and that fluoxetine exerts its antidepressant effect through enhancing the autophagic pathway by upregulation of the BDNF‐TrkB pathway . Therefore, our present data indicate that the contribution of the BDNF‐TrkB pathway to the antidepressant‐like roles of H 2 S in STZ‐induced diabetic rats is achieved by promoting hippocampal autophagy (Figure ).…”
Section: Discussionsupporting
confidence: 64%
“…Simultaneously, emerging evidence has indicated that exogenous H 2 S protects the heart and renal organs against ischaemic‐reperfusion injury in rats via increasing autophagy . Interestingly, it has been revealed that BDNF promotes neuron survival through improving autophagy and that fluoxetine exerts its antidepressant effect through enhancing autophagic pathway by upregulation of the BDNF‐TrkB pathway . Therefore, we would like to investigate whether the contribution of the BDNF‐TrkB pathway to antidepressant‐like effects of H 2 S in diabetic rats is achieved by enhancing hippocampal autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…it is well-known that autophagy is highly associated with the pathogenesis of depressive disorder (16). autophagy can eliminate damaged organelles and proteins, and is considered to be a conserved process that regulates catabolic processes, and it contributes to the maintenance of cellular energy homeostasis and regulation of cell growth (17).…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising since autophagy has been implicated in the regulation of neurogenesis, which is altered by psychological stress and represents a risk factor for the development of mood/neuropsychiatric disorders (63). In line with this, the administration of either antidepressant drugs or the naturally occurring autophagy inducer resveratrol alleviates depressive-like behavior in mice models of CUMS or post-partum depression by increasing BDNF and autophagyassociated proteins (136,138). This goes along with reduced HPA axis hyperactivity, CRF and pro-inflammatory cytokines levels (136,138).…”
Section: Impairment Of Lc-ne To Vta-da Neurons May Occlude Ne-inducedmentioning
confidence: 90%